The Effect of Levosimendan on Phosphine-Induced Nephrotoxicity: Biochemical and Histopathological Assessment - Baeeri, Maryam; Rahimifard, Mahban; Armandeh, Maryam; Bameri, Behnaz; Khalid, Madiha; Haghi-Aminjan, Hamed; Farhadi, Ramtin; Abdollahi, Mohammad (Drug Research, 2021)
Background Aluminum phosphide (AlP) toxicity is associated with a high risk of death due to heart, liver, and kidney failure as the target organs. Phosphine gas released due to the ingestion is the main factor involved in the multi-organ failure with various mechanisms. Levosimendan (LEV) is a calcium sensitizer with a pleiotropic effect on multiple organs. This study aimed to investigate whether LEV can alleviate AlP-induced nephrotoxicity in the rat model.Method Six groups included control group (almond oil only), sole LEV group (48 µg/kg), AlP group (LD50=10 µg/kg), and the poisoned groups treated with LEV at doses of 12, 24, and 48 µg/kg 30 min after AlP gavage. After 24 hours of treatment, serum and kidney samples were taken for biochemical and histopathological analyses.Result Biochemical analysis of the AlP group showed that the activity of complexes I, II, and IV was significantly reduced, while the levels of lipid peroxidation (LPO) and reactive oxygen species (ROS), lactate, and myeloperoxidase (MPO) activity significantly increased. Also, AlP reduced live renal cells and elevated necrosis. However, the levels of serum creatinine and blood urea nitrogen were not affected by the poisoning. LEV co-treatment could increase mitochondrial complex activity and reduce MPO activity, LPO, ROS, and lactate levels. Additionally, the histopathological analysis showed the detrimental effects of AlP on kidney tissue, which was mitigated by LEV administration.Conclusion Our findings showed that LEV can potentially improve oxidative stress, imbalance in the redox status, necrosis, and pathological injuries in kidney tissue following AlP-poisoning.
Keywords: Aluminum phosphide; levosimendan; mitochondria; nephrotoxicity; oxidative stress